EMBR-13. FAVORABLE OUTCOMES IN CHILDREN WITH PINEOBLASTOMA TREATED WITH RISK-ADAPTED CRANIOSPINAL IRRADIATION AND CHEMOTHERAPY: RESULTS AND MOLECULAR ANALYSIS FROM THE SJYC07 AND SJMB03 TRIALS. Issue 2 (22nd June 2018) - Liu, Anthony; Orr, Brent; Lin, Tong; Bouffet, Eric; Gururangan, Sridharan; Crawford, John; Kellie, Stewart J; Chintagumpala, Murali; Fisher, Michael; Bowers, Daniel C; Hassall, Tim; Ellison, David; et al.
Abstract: BACKGROUND: Pineoblastoma (PB) is an aggressive embryonal tumor that has been uniformly treated with high-dose craniospinal irradiation (CSI). Herein, we describe patients diagnosed with PB treated on 2 multi-center, prospective trials with risk-adapted radiation regimens. METHODS: Patients <3yr received chemotherapy with/without focal irradiation (SJYC07). Patients ≥3yr received risk-adapted CSI (23.4Gy for localized disease, 36–39.6Gy for metastatic) and chemotherapy (SJMB03). DNA methylation was performed using Infinium MethylationEPIC BeadChip and profiled on DKFZ molecularneuropathology2.0 classifier. RESULTS: 40 patients were enrolled (SJMB03=28; SJYC07=12) with 6.07yr median age (range: 0.37–20.4) and 3.8yr median follow-up (range: 0.37–13.1). Twenty-two were stratified as high-risk (HR). All 28 SJMB03 patients received CSI; 6 SJYC07 patients received focal RT and 6 were not irradiated. All but one patient received chemotherapy (parental refusal). On SJMB03, 10/11 non-HR patients receiving 23.4Gy CSI survived without progression (5yr-PFS 100%) as compared to 8/17 HR patients (5yr-PFS 56.3 ± 12.4%). On SJYC07, 11/12 progressed (5yr-PFS 8.3 ± 8.0%). 23/40 tumors (58%) were methylation profiled into the following categories: PBgroupB (N=11), PBgroupA (N=2), pineal parenchymal tumor (N=1), choroid plexus tumor (CPT) (subclass pediatric B) (N=1), with 6 samples having calibrated score <0.9 (associated with medulloblastomagroup3 =4, CPT=1, PBgroupB =1, no-match=2). All patients with PB-B were aged ≥3yr with 67% (8/12) surviving progression-free. Patients <3yr had PBgroupA /medulloblastoma/CPT and only 14% (1/7) survived progression-free. CONCLUSION: Non-metastatic PB in children ≥3yr has excellent survival with average-risk medulloblastoma therapy. The poor survival of young children and HR-PB might be explained by underlying molecular heterogeneity, and clustering of pineal tumors with MBgroup3 or CPT warrants further investigation.